AB0782 SECUKINUMAB PROVIDES IMPROVEMENTS IN HEALTH-RELATED QUALITY OF LIFE IN PATIENTS WITH PSORIATIC ARTHRITIS, REGARDLESS OF THE TIME SINCE DIAGNOSIS: POOLED RESULTS FROM THE SECUKINUMAB PHASE 3 TRIAL PROGRAM. (June 2019) - Strand, Vibeke; Fitzgerald, Oliver; Coates, Laura C.; Walsh, Jessica a.; Cañete, Juan D.; Nash, Peter; Davenport, Eric; Pricop, Luminita; Hustache, Gregory; Gilloteau, Isabelle; Yocolly, Aurore; Augustin, Matthias
Abstract : Background: Psoriatic arthritis (PsA) can have a profound impact on health-related quality of life (HRQoL). Secukinumab (SEC), a fully-human IL-17A inhibitor, has been shown to improve symptoms and HRQoL in patients (pts) with PsA. 1 Objectives: To evaluate the impact of SEC on HRQoL, assessed using the Short form-36 Health Survey (SF-36), in pts with PsA stratified by time since first diagnosis (<2 or ≥2 yrs). Methods: Pts were randomized to either subcutaneous placebo (PBO) or SEC 150 mg (FUTURE 2, 3, 4, 5), 150 mg no load (NL; FUTURE 4, 5), or 300 mg (FUTURE 2, 3, 5). Doses were administered at baseline (BL) and Wks 1–4, followed by every 4 wks (or every 4 wks from BL in NL groups). Pts on PBO were re-randomized to SEC at Wk 16 or 24. Mixed-models for repeated measures were used to assess changes from BL to Wk 16; observed data are presented at Wk 52. The proportion of pts reporting improvements ≥ minimum clinically important differences (MCID) in SF-36 physical (PCS responders), mental component summary (MCS responders), and individual SF-36 domains was also assessed. Non-responder imputation was employed for missing values in responder analyses. Fisher's exact test was used to compare the proportion of responders. Results: A total of 2049 pts were included: 681, 461, 572, and 335 in the PBO, SEC 300 mg, 150 mg, and 150 mg NL groups, respectively. Of these, 34%, 30%, 32%, and 33%, were classified as <2 yrs since PsA diagnosis (overall: 32%). Mean times since diagnosis were 0.8–0.9 yrs across treatment groups in the <2 yrs subgroup, and 8.6–10.1 yrs in the ≥2 yrs subgroup. The least squares mean (LSM) changes from BL to Wk 16 in PCS and MCS were significantly improved with all doses of SEC vs PBO in both <2 yrs (PCS: PBO = 0.8 vs 6.5 [p<0.0001], 4.8 [p<0.0001], 3.6 [p<0.01] for the 300 mg, 150 mg, and 150 mg NL groups, respectively; MCS: PBO = 1.3 vs 4.0 [p<0.01], 4.4 [p<0.01], 3.8 [p<0.05]) and ≥2 yrs since diagnosis (PCS: PBO = 1.9 vs 6.9 [p<0.0001], 5.3 [p<0.0001], 5.5 [p<0.0001]; MCS: PBO = 0.9 vs 3.6 [p<0.01], 2.8 [p<0.01], 3.0 [p<0.01]) groups. Improvements in individual SF-36 domains were reported with SEC vs PBO in the overall population and both subgroups (Figure). At Wk 16, the proportion of PCS responders was significantly higher with SEC vs PBO, in both <2 yrs (PBO: 38.5% vs 300 mg: 69.1% [p<0.0001]; 150 mg: 59.5% [p<0.01]; 150 mg NL: 53.6% [p<0.05]) and ≥2 yrs (PBO: 43.8%; 300 mg: 64.6% [p<0.0001]; 150 mg: 59.4% [p<0.01]; 150 mg NL: 65.8% [p<0.0001]) groups. Overall, improvements in SF-36 scores and MCID responses were generally more prominent with SEC 300 mg vs SEC 150 mg and in those <2 yrs vs ≥2 yrs from diagnosis. Improvements in PCS, MCS, individual domains, and MCID responses with SEC were sustained to Wk 52. Conclusion: SEC offered significant, clinically meaningful and sustained improvements in HRQoL (SF-36) in pts with PsA, regardless of time since diagnosis. References: [1] Mease PJ, et al. Ann Rheum Dis. 2018;77:890–7 Acknowledgement: This study was sponsored by Novartis Pharma aG. Medical writing support was provided by Seren Communications, an ashfield Company, a division of UDG, and was funded by Novartis. Disclosure of interests: Vibeke Strand Consultant for: Samumed, LLC, abbVie, amgen, EMD Serono, Eupraxia, Flexion, Iroko, Novartis, Pfizer, Regeneron, Sanofi, SKK, Oliver FitzGerald: None declared, Laura C Coates Grant/research support from: abbVie, Celgene, Lilly, Novartis and Pfizer, Consultant for: abbVie, amgen, BMS, Celgene, Galapagos, Gilead Sciences inc., Janssen, Lilly, Novartis, Pfizer, Prothena Corp and UCB, Jessica a. Walsh Grant/research support from: abbvie, Pfizer, Consultant for: abbvie, Celgene, Lilly, Novartis, Juan D. Cañete: None declared, Peter Nash Grant/research support from: abbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer inc, Roche, Sanofi, UCB, Consultant for: abbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer inc, Roche, Sanofi, UCB, Speakers bureau: abbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer inc, Roche, Sanofi, UCB, Eric Davenport Employee of: E. Davenport is an employee of RTI Health Solutions., Luminita Pricop Shareholder of: Novartis, Employee of: Novartis, Gregory Hustache Shareholder of: Novartis Pharma aG, Employee of: Novartis Pharma aG, Isabelle Gilloteau Employee of: Employee of Novartis, aurore Yocolly Employee of: Employee of Novartis, Matthias augustin Grant/research support from: Prof. Augustin has served as consultant and/or paid speaker for and/or has received research grants and/or honoraries for consulting and/or scientific lectures for and/or got travel expenses reimbursed and/or participated in clinical trials sponsored by companies that manufacture drugs used for the treatment of Psoriasis including abbVie, almirall, amgen, Biogen (Biogen Idec), Boehringer ingelheim, Celgene, Centocor, Eli Lilly, Galderma, Janssen-Cilag, Leo, Medac, MSD, Mundipharma, Novartis, Pfizer, Sandoz, Xenoport., Consultant for: Prof. Augustin has served as consultant and/or paid speaker for and/or has received research grants and/or honoraries for consulting and/or scientific lectures for and/or got travel expenses reimbursed and/or participated in clinical trials sponsored by companies that manufacture drugs used for the treatment of Psoriasis including abbVie, almirall, amgen, Biogen (Biogen Idec), Boehringer ingelheim, Celgene, Centocor, Eli Lilly, Galderma, Janssen-Cilag, Leo, Medac, MSD, Mundipharma, Novartis, Pfizer, Sandoz, Xenoport., Speakers bureau: Prof. Augustin has served as consultant and/or paid speaker for and/or has received research grants and/or honoraries for consulting and/or scientific lectures for and/or got travel expenses reimbursed and/or participated in clinical trials sponsored by companies that manufacture drugs used for the treatment of Psoriasis including abbVie, almirall, amgen, Biogen (Biogen Idec), Boehringer ingelheim, Celgene, Centocor, Eli Lilly, Galderma, Janssen-Cilag, Leo, Medac, MSD, Mundipharma, Novartis, Pfizer, Sandoz, Xenoport.